Patterns and physical principles of traditional houses in Kashan - Farzad Farnad; Hadiseh Kamran Kasmaei; Mehdi Khakzand; Gholamhossein Memarian (مسکن و محیط روستا)
To reach greater efficiency, traditional houses have experimentally achieved principles and patterns over time that are repeated explicitly or implicitly in all houses. Providing great harmony with the culture and climate of the region, some of these principles are used in a larger spatial or temporal range and some in a smaller range. The study aims to identify and study the principles and physical patterns of traditional houses in Kashan by providing examples. The research is applied and qualitative and uses descriptive and analytical methods based on case studies. Data collection was conducted through field surveys and studying written sources. The scope of the study is the traditional houses of Kashan in Jalali fort during the Qajar and First Pahlavi period. The case study consists of eight houses that were randomly selected from the collection of houses of the Kashan Cultural Heritage Organization. The findings of this study are categorized into three main patterns: the pattern of relationships with the surroundings and the city, the pattern of spatial arrangement and formation, the pattern of activity and functions. These patterns include eight principles: in harmony with the context, simplicity of the external body, negative space as a forming center, coherence of the positive space, sequential and articular spatial arrangement, confidentiality, variety of functional spaces, and multiple sides for different activities. The results of this research show how houses are formed based on the mentioned patterns and principles starting from the courtyard and evolving to the relationships with the city back and forth. By explaining these principles, this research can pave the way for recognizing other principles and patterns that shape traditional houses.